Alterations to Embryonic Serotonin Change Aggression and Fearfulness. Issue 2 (5th February 2013) - Dennis, Rachel L.; Fahey, Alan G.; Cheng, Heng W.
Abstract Prenatal stress can alter the serotonin (5‐HT) system in the developing and adult brain and lead to mood and behavioral disorders in children and adults. The chicken provides a unique animal model to study the effects of embryonic stressors on childhood and adolescent behavior. Manipulations to the egg can be made in the absence of confounding maternal effects from treatment. Eggs were injected with 50 μL of excess 5‐HT (10 μg/egg), 8‐OH‐DPAT (a 5‐HT1A receptor agonist; 16 μg/egg), or saline on day 0 prior to the 21 days incubation. Injections were performed at 0.5 cm below the shell. Behavior was analyzed at 9 weeks of age and again at the onset of sexual maturity (18 weeks). Hens treated with excess embryonic 5‐HT exhibited significantly less aggressive behaviors at 9 weeks of age compared to both 5‐HT1A agonist treated and saline hens (P < 0.05), and at 18 weeks of age compared to saline control birds only (P < 0.05). Excess embryonic 5‐HT also increased fearfulness response (P < 0.05) as tested by duration of tonic immobility. Increased degree of fluctuating asymmetry at 18 weeks in 5‐HT‐treated birds (P < 0.05) suggests that excess 5‐HT in early embryonic stages may create a developmental instability, causing phenotypic variations. These results showed that modification of the serotonergic system during early embryonic development alters its functions in mediating aggressive and fearful or anxious behaviors. Prenatal modification of the serotonergic system has long lived implications on both physiology and behavior, especially aggressive and fearful behaviors. Aggr. Behav. 39:91–98, 2013. Published in 2013 Wiley Periodicals, Inc.1